MASS MORTALITY OF CORALS AND REEF LIVING FEATURES AT CON DAO ARCHIPELAGO (VIETNAM) IN OCTOBER 2005 - Ben, Hoang Xuan; Tuan, Vo Si; Hoang, Phan Kim (Vietnam Journal of Marine Science and Technology, 2008)
Con Dao archipelago located in the southeastern waters of Vietnam at 8037’ – 8048’ N and 106032’ - 106045’ E is characterised by diverse terrestrial and marine ecosystems. Coral reefs occupy the area around 1000 ha with more than 320 hard corals species recorded. A catastrophe causing mass mortally of corals and reef leaving features occurred in October 2005. Almost coral reefs in the northeastern waters of the archipelago was impacted, indicating mortality of corals ranking from 20% to nearly 100%. The mass mortality is more serious in reef flats in comparison with that in reef slopes. All hard corals of genera Acropora, Leptoria, Platygyra, Montipora and Porites died in reef flats meanwhile Galaxea is more resilient to the impact. Almost non-movable benthic invertebrates also died and density of reef fish decreased seriously on impacted reefs. The analysis of water samples and the data recorded by the Station of Meteorology and Hydrology at Con Dao showed the reason of the catastrophe. Water temperature in Con Dao increased with temperature more than 300C in lots of days during October, especially more than 310C on 11th and 12th October. In the same time, salinity also reduced with value less than 25%o in 7 days. Combination impact of these two factors were considered as the reason for mass mortality in the event. A hypothesis that fresh water from river mouths of the Mekong river system was dispersed to the archipelago during this period was recommended for further surveys.